S10-2: Updating the German Recommendations for Physical Activity Promotion – Integration of Sector-Relatedness, Health Equity, and Planetary Health (Baltic Journal of Sport and Health Sciences, 2026)
Background: The German Recommendations (NEBB) for Physical Activity (PA) and PA Promotion (PAP) (Rütten & Pfeifer, 2016) have been identified by the Federal Ministry of Health as important framework for all stakeholders in the field (BMG, 2024). An update of the NEBB appears necessary, among other reasons, due to recent recommendations and action plans from the World Health Organization and the absence of guidelines for additional target groups (e.g. people with disabilities, pregnant women). Moreover, similar to other PA guidelines, the NEBB have not addressed issues related to planetary health.Methods: To integrate sector-relatedness, health equity, and planetary health into the PAP recommendations, a three-step process will be undertaken. First, recent evidence syntheses about PAP and impacts of PA on planetary health will be compiled. Second, expert interviews with scientists and stakeholders will be conducted. The purpose of these interviews is to learn from the experiences of other research fields (e.g. diet/nutrition) about how to address the mentioned issues in PAP guidelines, and also to explore the ethical considerations of balancing individual health benefits from PA with potential planetary health drawbacks. In the third step, various stakeholders shall participate in a co-production approach to discuss and translate the findings in concrete PAP recommendations for relevant societal sectors, such as health, sport, traffic, etc.Results: The revised German PA promotion recommendations will include guidelines for stakeholders on how to promote PA in relevant societal/political sectors, also in a sustainable manner. Regarding planetary health however, it remains unclear whether this will be achieved by emphasising the co-benefits of certain types of PA (e.g. active transport) or by more directly addressing the negative environmental impacts of certain types of PA. The presentation will outline the results of the expert interviews (step 2) and discuss different options of the recommendations, also for integrating planetary health considerations.Conclusion: Until now, many PAP efforts have focused on target groups, adhering to the goal statement ‘every step counts’. Thus, they may have neglected sector-related factors and also avoided any mention of potential harmful environmental impacts of PA. Addressing these issues in PAP recommendations further raises practical and ethical challenges.Keywords: Physical activity, physical activity promotion, planetary health